Design and Parameter Optimization of Spiral-Dragon Type Straw Chopping Test Rig - Ma, Pengbo; Li, Liqiao; Wen, Baoqin; Xue, Yunheng; Kan, Za; Li, Jingbin (International Journal of Agricultural and Biological Engineering, 2020)
In order to address the problems of large chop length, high energy consumption and poor chopping effect that were associated with a horizontal total mixed rations (TMR) mixer, a straw chopping device was designed; further, its structure and working principle were analyzed. In this study, wheat straw was chosen as the test object. The number of processing times, number of fixed blades, cutting speed, number of tooth plates and the inclined angle of the box were considered as the test factors. The standard straw length rate and average power were used as evaluation indices for conducting the orthogonal rotation combination experiment with five factors and five levels of quadratic regression. The experimental results denoted that the order of influencing factors on the standard straw length rate can be given as follows: the number of processing times, number of fixed blades, cutting speed, number of tooth plates and inclined angle of the box. The order of the influence of each factor on the average power can be given as follows: the cutting speed, number of fixed blades and number of tooth plates. Further, the optimum structural and working parameters of the device can be determined as follows: linear cutting speed of 17-20 m/min, box inclined angle of 70°-80°, 20-23 fixed blades, 5-6 processing times and 4-7 tooth plates. Under such a circumstance, the standard straw length rate reached up to 70.5%-77.4% and the average power was low at 5.8-7 kW. The results can be used as reference for designing a chopping device for a TMR mixer. Keywords: total mixed rations, straw, chopping device, parameter optimization DOI: 10.25165/j.ijabe.20201301.4927 Citation: Ma P B, Li L Q, Wen B Q, Xue Y H, Kan Z, Li J B. Design and parameter optimization of spiral-dragon type straw chopping test rig. Int J Agric & Biol Eng, 2020; 13(1): 47–56.